RANCANG BANGUN ROLLER BENDER MANUAL - Rifqi Marzuqi Zain, - (2019)
This Final Project discusses the making of a manual roller bender to determine the time and cost required to manufacture a manual roller bender component, in making the material used is ST37. The process of making this manual roller bender component includes: 1. the drilling process, 2. the turning process 3. the welding process 4.roller bender manual design. Theoretically the total time and production cost needed is Rp. 523.488,00 Tugas Akhir ini membahas tentang pembuatan roller bender manual untuk mengetahui waktu dan biaya yang dibutuhkan untuk pembuatan komponen roller bender manual , dalam pembuatannya material yang digunakan adalah ST37. Proses pembuatan komponen roller bender manual ini meliputi : 1. proses pengeboran, 2. proses pembubutan 3.proses pengelasan 4.Perancangan roller bender manual. Secara teoritis total waktu dan biaya produksi yang dibutuhkan adalah Rp. 523.488,00.